Method and device for testing cross-linking curing degree of film layer on surface of strip steel

By comparing the ratio of the reference porosity of the film layer on the surface of the strip and the porosity of the sample to be tested, the problem of low testing efficiency and accuracy in the existing technology is solved, and the degree of cross-linking and solidification of the film layer on the surface of the strip is quickly and accurately determined. Assessment to help steel mills improve product quality and production efficiency.

CN119354839AActive Publication Date: 2025-01-24武汉钢铁有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411360818.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-24
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

In the prior art, the test efficiency and accuracy of the cross-link curing degree of the strip surface film layer is low, resulting in uneven film quality and affecting product performance.

Method used

By obtaining the reference membrane pore rate of the steel sample and the membrane layer pore rate of the steel sample to be tested, calculate and compare the ratio of the two to determine the degree of linked solidification of the membrane layer. Specific methods include chemical solvent treatment and tape pulling treatment to determine the pore rate of the membrane layer.

Benefits of technology

It improves the test efficiency and accuracy of the degree of curing of the intersection of the lapse of the steel, which can quickly and accurately evaluate the degree of linked solidification of the membrane layer, help steel mills to adjust the processing process, reduce quality problems, and improve production efficiency and profits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119354839A_ABST
    Figure CN119354839A_ABST
Patent Text Reader

Abstract

The invention discloses a method and device for testing the cross-linking curing degree of a film layer on the surface of strip steel, and the method is characterized in that the method comprises the steps: obtaining the film layer porosity of a first strip steel sample coated with the film layer, defining the film layer porosity as a reference film layer porosity, and enabling the cross-linking curing degree of the film layer on the surface of the first strip steel sample to meet the industrial production requirements; a first to-be-detected strip steel sample is subjected to chemical solvent treatment, the membrane layer porosity of the first to-be-detected strip steel sample is obtained and defined as the first sample membrane layer porosity, and the first to-be-detected strip steel sample is obtained from an actual production line; and determining a first porosity ratio between the first sample porosity and the reference porosity, and judging whether the surface film layer of the first to-be-detected strip steel sample is insufficient in cross-linking curing or not based on the first porosity ratio. According to the technical scheme, the efficiency and accuracy of testing the cross-linking curing degree of the strip steel surface film layer can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal material surface testing, and in particular to a method and device for testing the cross-linking and curing degree of a film layer on a strip surface. Background Art

[0002] The post-processing of strip steel is a process of coating a specific functional coating on the surface of cold-rolled or electrical steel products and drying it at high temperature to cross-link and solidify the components in the coating to form a dense film layer. Different coatings can improve the corrosion resistance, moisture and heat resistance, insulation, stamping lubricity and surface appearance of strip steel products, and are widely used in automobiles, home appliances, office supplies, generators and transformers. In the post-processing process of strip steel, high-temperature drying and cross-linking curing after coating is one of the key processes affecting the quality of the film layer. Low-temperature preheating treatment is required at the initial stage of curing to steadily volatilize the water and low-boiling point solvent in the coating. If the preheating temperature is too low, the solvent evaporates too slowly, resulting in uneven film thickness; if the temperature is too high, the solvent evaporates too quickly, the film layer is prone to cracking and void defects. The preheating time also needs to be moderate. If the time is too short, the residual water and solvent will not be completely volatilized. If the time is too long, the water will evaporate before the coating is completely cured, resulting in powdery film. The high-temperature baking curing after preheating allows the components in the coating liquid to fully cross-link and combine with the base material to form a complete film layer to achieve the expected performance. The temperature and time of baking and curing determine the final performance of the film layer. If the temperature or time is insufficient, the resin cross-linking reaction is not sufficient, which will lead to a decrease in the density, adhesion and mechanical properties of the film layer. In severe cases, the plate surface will stick after curling. If the temperature is too high or the time is too long, although the density and hardness of the film layer are improved, the color, luster, flexibility and adhesion will deteriorate, and defects such as powdering, orange peel, pinholes and poor adhesion may occur. Therefore, efficient and accurate testing of the performance of the film layer on the surface of the strip and strict control of the cross-linking and curing degree of the strip film layer are the key to ensuring the application performance of the strip product.

[0003] However, the current testing scheme for the performance of the film layer on the strip surface in the production line is not yet mature, resulting in low testing efficiency and accuracy of the cross-linking and curing degree of the film layer on the strip surface. Based on this, how to improve the efficiency and accuracy of testing the cross-linking and curing degree of the film layer on the strip surface is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The embodiments of the present application provide a method and device for testing the degree of cross-linking and curing of a film layer on the surface of a steel strip, thereby improving the efficiency and accuracy of testing the degree of cross-linking and curing of a film layer on the surface of a steel strip.

[0005] Other features and advantages of the present application will become apparent from the following detailed description, or may be learned in part by the practice of the present application.

[0006] According to the first aspect of an embodiment of the present application, a method for testing the degree of cross-linking and curing of a surface film layer of a steel strip is provided, the method comprising: obtaining the film layer porosity of a first steel strip sample coated with a film layer, defined as a reference film layer porosity, and the degree of cross-linking and curing of the surface film layer of the first steel strip sample meets industrial production requirements; subjecting a first steel strip sample to be tested to a chemical solvent treatment, and obtaining the film layer porosity of the first steel strip sample to be tested, defined as a first sample film layer porosity, and the first steel strip sample to be tested is obtained from an actual production line; determining a first porosity ratio between the first sample porosity and the reference film layer porosity, and judging whether the surface film layer of the first steel strip sample to be tested has insufficient cross-linking and curing based on the first porosity ratio.

[0007] In some embodiments of the present application, based on the aforementioned scheme, the method also includes: if the first steel strip sample to be tested does not have insufficient cross-linking and curing of the surface film layer, performing tape pulling treatment on the second steel strip sample to be tested, and obtaining the film layer porosity of the second steel strip sample to be tested, which is defined as the second sample film layer porosity, and the second steel strip sample to be tested is produced from the same production line as the first steel strip sample to be tested; determining a second porosity ratio between the porosity of the second sample and the reference porosity, and judging whether the surface film layer of the second steel strip sample to be tested is excessively cross-linked and cured based on the second porosity ratio.

[0008] In some embodiments of the present application, based on the aforementioned scheme, the film porosity of the first steel strip sample coated with a film layer is obtained, which is defined as a reference film porosity, and includes: degreasing, cleaning and drying the second steel strip sample not coated with a film layer; measuring the first polarization curve spectrum of the second steel strip sample by an electrochemical measuring device, and fitting the first polarization curve spectrum to obtain the first corrosion current of the second steel strip sample; preparing the second steel strip sample into the first steel strip sample; measuring the second polarization curve spectrum of the first steel strip sample by an electrochemical measuring device, and fitting the second polarization curve spectrum to obtain the second corrosion current of the first steel strip sample; calculating the ratio of the second corrosion current to the first corrosion current as the reference film porosity.

[0009] In some embodiments of the present application, based on the aforementioned scheme, the preparation of the second steel strip sample into the first steel strip sample includes: re-degreasing, cleaning and drying the second steel strip sample; applying a film layer to the surface of the second steel strip sample by scraping with a scraper; and cross-linking and curing the second steel strip sample after the film layer is coated to obtain the first steel strip sample whose cross-linking and curing degree meets the requirements of industrial production.

[0010] In some embodiments of the present application, based on the aforementioned scheme, the first steel strip sample to be tested is subjected to a chemical solvent treatment, and the film porosity of the first steel strip sample to be tested is obtained, which is defined as the first sample film porosity, including: the first steel strip sample to be tested is subjected to a chemical solvent treatment to remove the film raw material that is not solidified on the surface of the first steel strip sample to be tested; the third polarization curve spectrum of the first steel strip sample to be tested is measured by an electrochemical measuring device, and the third polarization curve spectrum is fitted to obtain the third corrosion current of the first steel strip sample to be tested; and the ratio of the third corrosion current to the first corrosion current is calculated as the first sample film porosity.

[0011] In some embodiments of the present application, based on the aforementioned scheme, determining whether the surface film layer of the first steel strip sample to be tested has insufficient cross-linking and curing based on the first porosity ratio includes: if the first porosity ratio is less than the first porosity ratio threshold, determining that the sample to be tested has insufficient cross-linking and curing.

[0012] In some embodiments of the present application, based on the aforementioned scheme, the second steel strip sample to be tested is subjected to a tape pulling treatment, and the film porosity of the second steel strip sample to be tested is obtained, which is defined as the second sample film porosity, including: performing a tape pulling treatment on the second steel strip sample to be tested to peel off the defective portion of the film layer that is not attached to the surface of the second steel strip sample to be tested; measuring the fourth polarization curve spectrum of the second steel strip sample to be tested by an electrochemical measuring device, and fitting the fourth polarization curve spectrum to obtain the fourth corrosion current of the second steel strip sample to be tested; calculating the ratio of the fourth corrosion current to the first corrosion current as the second sample film porosity.

[0013] In some embodiments of the present application, based on the aforementioned scheme, the determination of whether the surface film layer of the second steel strip sample to be tested is excessively cross-linked and cured based on the second porosity ratio includes: if the second porosity ratio is less than the second porosity ratio threshold, determining that the second steel strip sample to be tested is excessively cross-linked and cured.

[0014] According to a second aspect of the present application, an electrochemical measuring device is provided, characterized in that it is applied to the method described in any one of the embodiments of the first aspect above.

[0015] In some embodiments of the present application, based on the aforementioned scheme, the device includes: an electrolytic cell, which is cylindrical, with an open upper end and a cover, and a closed lower end with a hole; a portable electrochemical workstation, used to record measurement data and draw a polarization curve spectrum; a sealing ring, arranged at the closed hole at the lower end of the electrolytic cell; a platinum mesh electrode, a reference electrode and a working electrode clamp, which are used to connect the electrolytic cell and the portable electrochemical workstation and perform data measurement; an electrolytic cell cover, which is arranged at the open upper end of the electrolytic cell and is used to fix the platinum mesh electrode and the reference electrode.

[0016] Based on the technical solution proposed in this application, by obtaining the reference porosity of the steel strip sample and the sample porosity of the steel strip sample to be tested, the reference film porosity is used as a benchmark to improve the accuracy and reliability of the comparison. By using the film porosity to characterize the state of the film layer on the surface of the steel strip, and then taking the ratio of the sample film porosity to the reference film porosity, the cross-linking and curing degree of the surface film layer is determined by the ratio. This method is not only simple to operate, but also can improve the efficiency and accuracy of testing the cross-linking and curing degree of the steel strip surface film layer.

[0017] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 An electrochemical measuring device according to an embodiment of the present application is shown;

[0020] Figure 2 A schematic flow chart of a method for testing the cross-linking and curing degree of a film layer on a surface of a steel strip according to an embodiment of the present application is shown. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0022] In addition, described feature, structure or characteristic can be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present application. However, those skilled in the art will appreciate that the technical scheme of the present application can be put into practice without one or more of the specific details, or other methods, components, devices, steps, etc. can be adopted. In other cases, known methods, devices, realizations or operations are not shown or described in detail to avoid blurring the various aspects of the application.

[0023] The block diagrams shown in the accompanying drawings are merely functional entities and do not necessarily correspond to physically independent entities. That is, these functional entities may be implemented in software form, or in one or more hardware modules or integrated circuits, or in different networks and / or processor devices and / or microcontroller devices.

[0024] The flowcharts shown in the accompanying drawings are only exemplary and do not necessarily include all the contents and operations / steps, nor must they be executed in the order described. For example, some operations / steps can be decomposed, and some operations / steps can be combined or partially combined, so the actual execution order may change according to actual conditions.

[0025] It should be noted that the "multiple" mentioned in this article refers to two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships can exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0026] In order to enable those skilled in the art to better understand the present solution, a brief introduction is first given to the electrochemical testing principle based on the porosity of the membrane layer.

[0027] The present application is based on the electrochemical test of the film porosity. The corrosion current can be obtained by fitting the polarization curve spectrum, and then the porosity of the film sample on the surface of the strip steel is calculated. The film porosity is the ratio of the corrosion current of the strip steel with the film layer to the corrosion current of the strip steel without the film layer. The smaller the porosity, the fewer the pores in the film layer. It is difficult for the corrosive medium to penetrate the film layer and directly contact the strip steel to react electrochemically. The corresponding corrosion current is also very small. The larger the porosity, the more pores in the film layer. The corrosive medium is easy to penetrate the film layer and directly contact the strip steel to react electrochemically. The corresponding corrosion current is larger and closer to the value of the corrosion current of the strip steel without the film layer. Among them, the corrosive medium can refer to the electrolyte solution added when the electrochemical measuring device is measuring.

[0028] If the film is not cross-linked and cured enough, it may lead to poor density, uneven coating, poor adhesion and other problems. At this time, the porosity of the film will be greater than the porosity of the film when the cross-linking and curing is qualified. When the film is wiped with cotton wool soaked in butanone, the raw materials of the film that have not reacted thoroughly on the surface of the strip are easily removed, which will further increase the porosity of the film with insufficient cross-linking and curing. If the film is excessively cross-linked and cured, it may lead to powdering, shrinkage, poor adhesion and other problems. At this time, the porosity of the film will also be greater than the porosity of the film when the cross-linking and curing is qualified. When the cross-linked and cured film is wiped with cotton wool soaked in butanone, it will not cause film loss. When the test tape is used to stick such a film, the defective part will be peeled off, which will further increase the porosity of the film.

[0029] In order to make those skilled in the art better understand this scheme, the following will be combined with Figure 1 The electrochemical measuring device of this embodiment will be described.

[0030] See also Figure 1 , shows an electrochemical measuring device according to an embodiment of the present application.

[0031] like Figure 1 As shown, the electrochemical device includes an electrolytic cell 101, which is cylindrical, with an open upper end and a cover, and a closed lower end with a hole; a portable electrochemical workstation 105, which is used to record measurement data and draw a polarization curve spectrum; a sealing ring 107, which is arranged at the closed hole at the lower end of the electrolytic cell; a platinum mesh electrode 103, a reference electrode 104 and a working electrode clamp 106, which are used to connect the electrolytic cell and the portable electrochemical workstation and perform data measurement; an electrolytic cell cover 102, which is arranged at the open upper end of the electrolytic cell and is used to fix the platinum mesh electrode and the reference electrode; a tested strip steel substrate 108A; and a surface film layer 108B of the strip steel substrate.

[0032] The following is a detailed description of the implementation details of the solution for testing the cross-linking and curing degree of the steel strip surface film layer according to the embodiment of the present application:

[0033] Figure 2 A schematic flow chart of a method for testing the cross-linking and curing degree of a film layer on a surface of a steel strip according to an embodiment of the present application is shown.

[0034] Reference Figure 2 The method for testing the cross-linking and curing degree of the film layer on the surface of the steel strip can be performed at least according to the following steps 210 to 230:

[0035] Step 210, obtaining the film porosity of the first steel strip sample coated with the film layer, which is defined as the reference film porosity, and the cross-linking and curing degree of the film layer on the surface of the first steel strip sample meets the industrial production requirements.

[0036] Step 220, subjecting the first steel strip sample to be tested to chemical solvent treatment, and obtaining the film layer porosity of the first steel strip sample to be tested, which is defined as the first sample film layer porosity, wherein the first steel strip sample to be tested is obtained from an actual production line.

[0037] Step 230, determining a first porosity ratio between the porosity of the first sample and the porosity of the reference film layer, and determining whether the surface film layer of the first steel strip sample to be tested has insufficient cross-linking and curing based on the first porosity ratio.

[0038] In the present application, the first steel strip sample can be a sample that meets industrial production standards and is produced outside the production line through standardized operating techniques and reasonable processes; the first steel strip sample to be tested can be a sample obtained from a product that has been produced in the production line and has not yet been tested.

[0039] In the present application, it should be noted that the film porosity is used to characterize the amount of pores in the film layer on the surface of the strip steel; the reference film layer porosity is the film layer porosity of the first strip steel sample, which can be used as a reference standard; by determining the ratio of the film layer porosity of the strip steel sample to be tested to the reference film layer porosity, it is determined whether the degree of cross-linking and curing on the surface of the strip steel sample to be tested is qualified.

[0040] In the present application, it is also necessary to explain that if the cross-linking and curing of the film layer on the surface of the strip steel is insufficient, the film layer raw materials that have not been completely reacted on the surface of the film layer can be removed after being treated with a chemical solvent, so that the porosity of the film layer is further expanded, and the accuracy of the test is improved. For example, in a specific embodiment of the present application, the film layer is wiped with absorbent cotton soaked with butanone, and the resin raw materials that have not been completely reacted on the film layer are easily wiped off, thereby expanding the porosity of the surface film layer.

[0041] Based on the above steps, the method for testing the cross-linking and curing degree of the film layer on the surface of the steel strip can also be specifically performed through the following steps 240 to 250:

[0042] Step 240: If the first steel strip sample to be tested does not have insufficient cross-linking and curing of the surface film layer, the second steel strip sample to be tested is subjected to tape pulling treatment, and the film layer porosity of the second steel strip sample to be tested is obtained, which is defined as the second sample film layer porosity. The second steel strip sample to be tested is produced from the same production line as the first steel strip sample to be tested.

[0043] Step 250, determining a second porosity ratio between the porosity of the second sample and the reference porosity, and determining whether the surface film layer of the second steel strip sample to be tested is excessively cross-linked and cured based on the second porosity ratio.

[0044] In the present application, it should be noted that it is necessary to first test whether the strip surface film layer has insufficient cross-linking and curing, and then test whether the strip surface film layer has excessive cross-linking and curing; the reason is that when testing the strip sample for insufficient cross-linking and curing, the chemical reagent treatment method cannot cause damage to the surface film layer that has undergone excessive cross-linking and curing, and when testing the strip surface film layer for excessive cross-linking and curing, the tape pulling treatment method can not only damage the excessive cross-linking and curing surface film layer, but also damage the insufficient cross-linking and curing surface film layer. Based on this, if the tape pulling treatment is performed first, it is impossible to determine whether the strip surface film layer has insufficient cross-linking and curing or excessive cross-linking and curing. Therefore, the present application creatively proposes a test sequence of first testing the strip surface film layer for insufficient cross-linking and curing, and then testing the strip surface film layer for excessive cross-linking and curing, which can greatly improve the efficiency and accuracy of testing the degree of cross-linking and curing of the strip surface film layer.

[0045] In the above step 210, the porosity of the film layer of the first steel strip sample coated with the film layer is obtained, which is defined as the reference film layer porosity. Specifically, the porosity can be performed according to the following steps 211 to 215:

[0046] Step 211, degreasing, cleaning and drying the second steel strip sample without coating layer.

[0047] Step 212: measure the first polarization curve spectrum of the second steel strip sample by an electrochemical measuring device, and perform fitting processing on the first polarization curve spectrum to obtain a first corrosion current of the second steel strip sample.

[0048] Step 213: prepare the second steel strip sample into the first steel strip sample.

[0049] Step 214: measure the second polarization curve spectrum of the first steel strip sample by an electrochemical measuring device, and perform fitting processing on the second polarization curve spectrum to obtain a second corrosion current of the first steel strip sample.

[0050] Step 215, calculating the ratio of the second corrosion current to the first corrosion current as the reference film layer porosity.

[0051] In the present application, it should be noted that the porosity of the film layer is defined as the ratio of the corrosion current of the strip steel coated with the film layer to the corrosion current of the strip steel not coated with the film layer. If there are more pores in the film layer on the surface of the strip steel, the corrosion current will be greater and the corresponding film layer porosity will also be greater.

[0052] In the present application, it should also be noted that the second steel strip sample may be a steel strip sample that is not coated with a surface film layer.

[0053] In the present application, the corrosion current can be measured by an electrochemical measuring device. In a specific embodiment of the present application, the electrochemical measuring device is placed on the surface of the strip steel after degreasing, cleaning and drying, and then a pre-configured 2-4% NaCl solution is added to the electrolytic cell, and the injection amount is about 700 ml. Then the platinum electrode mesh and the reference electrode are fixed on the electrolytic cell cover and connected to the portable electrochemical workstation. After the electrolytic cell cover is covered on the upper end of the electrolytic cell, the working electrode chuck is clamped on the edge of the strip steel. If the strip steel has a surface film layer, part of the surface film layer needs to be polished off to expose the surface of the strip steel, and then the working electrode chuck is connected to the electrochemical workstation. After completing the connection of the three-electrode system, the polarization curve measurement can be started according to the pre-set test parameters. The test parameters are: dynamic potential polarization curve scanning speed 5mv / s-10mv / s, potential scanning range: -0.75v~0.75v or -1~1v or -1.25~1.25v (relative to the reference electrode potential), and the test time is 4~9min. Finally, the corrosion current is obtained by fitting the polarization curve spectrum.

[0054] In the present application, it is also necessary to explain that when measuring the corrosion current, the measurement can be carried out on at least 3 separately prepared strip steel specimens, and the average value of the measured corrosion current can be calculated. If the absolute deviation of the corrosion current of one of the test results is greater than the average value of the corrosion current × 10%, the data is deemed invalid and additional testing is required.

[0055] In the above step 213, the second steel strip sample is prepared into the first steel strip sample, which can be specifically performed according to the following steps 2131 to 2133:

[0056] Step 2131, degrease, clean and dry the second steel strip sample again.

[0057] Step 2132, coating the surface of the second steel strip sample with a film layer by scraping with a scraper.

[0058] Step 2133, cross-linking and curing the second steel strip sample after the coating film layer is applied to obtain the first steel strip sample whose cross-linking and curing degree meets the requirements of industrial production.

[0059] In this application, it should be noted that the temperature and time for cross-linking and curing the coated film layer need to be determined according to the raw materials of the coated film layer, and the baking time for cross-linking and curing can be operated according to the recommended time in the coating manual. When heating the strip steel sample after coating, it should be noted that the heating furnace should be turned on in advance for preheating, and the furnace temperature can be set to the curing temperature recommended in the coating manual and maintained for 30 minutes.

[0060] In the above step 220, the first steel strip sample to be tested is subjected to chemical solvent treatment, and the film layer porosity of the first steel strip sample to be tested is obtained, which is defined as the first sample film layer porosity. Specifically, the steps 221 to 223 are performed as follows:

[0061] Step 221 , performing chemical solvent treatment on the first steel strip sample to be tested to remove the film layer material that is not solidified on the surface of the first steel strip sample to be tested.

[0062] Step 222: measuring a third polarization curve spectrum of the first steel strip sample to be tested by an electrochemical measuring device, and performing fitting processing on the third polarization curve spectrum to obtain a third corrosion current of the first steel strip sample to be tested.

[0063] Step 223, calculating the ratio of the third corrosion current to the first corrosion current as the porosity of the first sample film layer.

[0064] In the present application, the first steel strip sample to be tested is treated with a chemical solvent. In a specific embodiment, the following steps can be followed: a cotton ball soaked in butanone solution is used to wipe the test area on the surface of the first steel strip sample to be tested where the electrochemical measuring device is placed. The test area is a square area of ​​approximately 6×6 cm. It should be noted that the tweezers holding the cotton ball must be equipped with a rubber protective cover to prevent the tweezers from scratching the surface film layer of the first steel strip sample to be tested. The angle between the tweezers and the first steel strip sample to be tested is 40° to 50°, and a pressure of 500N to 700N is applied. The wiping frequency can be 1 to 2 round trips per second. After a total of 10 to 15 round trips, stop wiping and use a cold air blower to dry the residual butanone reagent on the surface. Through this method, the film layer material that has not solidified on the surface of the first steel strip sample to be tested can be removed.

[0065] In the present application, it should be noted that the third corrosion current can be obtained by measuring the corrosion currents on at least three steel strip samples to be tested, and then calculating the average value of all the measured corrosion currents. If the absolute deviation of one of the corrosion current data is greater than the average value of the corrosion current × 10%, the data is deemed invalid and additional testing is required until the data meets the requirements.

[0066] In the above step 230, the determination of whether the surface film layer of the first steel strip sample to be tested has insufficient cross-linking and curing based on the first porosity ratio may be performed according to the following step 231:

[0067] Step 231: If the first porosity ratio is less than a first porosity ratio threshold, it is determined that the sample to be tested is insufficiently cross-linked and cured.

[0068] In the present application, it should be noted that the letter α is used to represent the first porosity ratio. The relationship between the first porosity ratio and the first porosity ratio threshold value, in a specific embodiment, can be that when α≥0.96, it is determined that the surface film layer of the first steel strip sample to be tested has no insufficient cross-linking and curing; when 0.9≤α<0.96, it is determined that the surface film layer of the first steel strip sample to be tested has slightly insufficient cross-linking and curing; when 0.82≤α<0.9, it is determined that the surface film layer of the first steel strip sample to be tested has moderate insufficient cross-linking and curing; when α<0.82, it is determined that the surface film layer of the first steel strip sample to be tested has severe insufficient cross-linking and curing. If the result shows that the post-treatment film layer has slight, moderate or severe insufficient cross-linking and curing, subsequent testing may not be performed.

[0069] In the above step 240, the second steel strip sample to be tested is subjected to a tape drawing process, and the film layer porosity of the second steel strip sample to be tested is obtained, which is defined as the second sample film layer porosity. Specifically, the process can be performed according to the following steps 241 to 243:

[0070] Step 241 , performing a tape pulling process on the second steel strip sample to be tested, so as to peel off the defective portion of the film layer that is not attached to the surface of the second steel strip sample to be tested.

[0071] Step 242: measure the fourth polarization curve spectrum of the second steel strip sample to be tested by an electrochemical measuring device, and perform fitting processing on the fourth polarization curve spectrum to obtain a fourth corrosion current of the second steel strip sample to be tested.

[0072] Step 243, calculating the ratio of the fourth corrosion current to the first corrosion current as the porosity of the second sample film layer.

[0073] In the present application, the second steel strip sample to be tested is subjected to a tape pulling process. In a specific embodiment, 3M Scotch 600 100-grid test tape can be used to stick and pull the test area where the electrochemical measuring device is placed. The test area is a square area of ​​approximately 6×6 cm. The tape is covered on the surface of the second steel strip sample to be tested and a pressure of 500-700N is applied to wipe it. The wiping frequency can be 1-2 round trips per second. After a total of 5-10 round trips, the wiping is stopped, and the tape is lifted at a speed of 1-3 cm / s. Through this method, the defective part of the film layer that is not attached to the surface of the second steel strip sample to be tested can be peeled off.

[0074] In the present application, it should be noted that the fourth corrosion current can be measured on at least three steel strip samples to be tested, and then the average value of all measured corrosion currents is obtained. If the absolute deviation of one of the corrosion current data is greater than the average value of the corrosion current × 10%, the data is deemed invalid and additional testing is required until the data meets the requirements.

[0075] In the above step 250, the determination of whether the surface film layer of the second steel strip sample to be tested is excessively cross-linked and cured based on the second porosity ratio may be performed according to the following step 251:

[0076] Step 251: If the second porosity ratio is less than a second porosity ratio threshold, it is determined that the second steel strip sample to be tested has excessive cross-linking and curing.

[0077] In the present application, it should be noted that the letter β is used to represent the second porosity ratio. The relationship between the second porosity ratio and the second porosity ratio threshold value, in a specific embodiment, can be that when β≥0.92, it is judged that the surface film layer of the second steel strip sample to be tested has no excessive cross-linking and curing; when 0.84≤β<0.92, it is judged that the surface film layer of the second steel strip sample to be tested is slightly excessively cross-linked and cured; when 0.75≤α<0.84, it is judged that the surface film layer of the second steel strip sample to be tested is moderately excessively cross-linked and cured; when α<0.75, it is judged that the surface film layer of the second steel strip sample to be tested is severely excessively cross-linked and cured.

[0078] In the present application, an electrochemical measurement device is proposed, the device comprising: an electrolytic cell, the electrolytic cell is cylindrical, the upper end is open with a cover, and the lower end is closed with a hole; a portable electrochemical workstation, used to record measurement data and draw polarization curve spectra; a sealing ring, arranged at the closed hole at the lower end of the electrolytic cell; a platinum mesh electrode, a reference electrode and a working electrode chuck, used to connect the electrolytic cell and the portable electrochemical workstation and perform data measurement; an electrolytic cell cover, arranged at the upper end of the electrolytic cell, used to fix the platinum mesh electrode and the reference electrode. The device can be applied to the method as described above.

[0079] In order to make those skilled in the art better understand the present application, the inventive concept of the present application is described below in conjunction with some specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not used to limit the scope of the present application. The experimental method of the unrecorded specific conditions in the following examples is usually measured according to national standards. If there is no corresponding national standard, then according to general international standards, normal conditions, or according to the conditions recommended by the manufacturer, proceed.

[0080] Example 1

[0081] A galvanizing unit in a cold rolling mill plans to produce common galvanized products DX51-Z. Three samples of this steel without post-treatment, namely, the second steel strip samples, are obtained and degreased and dried. The electrochemical measuring device described in this application is placed on the surface of the second steel strip sample, and then a pre-configured 3.5% NaCl solution is added to the electrolytic cell with an injection volume of about 700 ml. Then, the electrolytic cell cover with a platinum electrode mesh and a reference electrode is installed and connected to a portable electrochemical workstation. The working electrode chuck is clamped on the edge of the second steel strip sample and connected to the portable electrochemical workstation. After the three-electrode system is connected, the polarization curve measurement can be started. The test parameters are: dynamic potential polarization curve scanning speed 5mv / s, potential scanning range: -1~1v (relative to the reference electrode potential), and test time: 400s.

[0082] The first polarization curve spectra of the three second steel strip samples were fitted and averaged to obtain the first corrosion current I0=5.1×10 -5 A / cm 2 .

[0083] A post-processing standard sample was prepared for the second steel strip sample. First, the second steel strip sample was degreased, cleaned and blown dry, and then a single-sided coating of a certain type of coating was performed on the surface of the second steel strip sample using a 5μm scraper. The second steel strip sample was immediately placed in an automatic temperature and time controlled film layer oven for cross-linking and curing. The baking temperature was 180°C and the curing time was 2 minutes.

[0084] The prepared DX51-Z sample with a reference surface film layer, i.e., the first steel strip sample, is subjected to polarization curve measurement using the electrochemical testing device described in the present application. During the test, the electrolytic cell is first placed on the surface of the first steel strip sample, and the pre-configured 3.5% NaCl solution is added to the electrolytic cell, with an injection volume of about 700 ml, and then the electrolytic cell cover with a platinum electrode mesh and a reference electrode is installed and connected to a portable electrochemical workstation. In addition, the edge of the surface of the first steel strip sample needs to be selected to grind off part of the film layer to expose the steel strip surface, and the working electrode chuck is clamped on the exposed part of the steel strip, and is also connected to the electrochemical workstation. After the electrolyte is injected into the electrolytic cell, the polarization curve measurement is started after standing for 5 minutes. The test parameters are: dynamic potential polarization curve scanning speed 5mv / s, potential scanning range: -1~1v (relative to the reference electrode potential), and test time: 400s.

[0085] The second polarization curve spectrum of the first steel strip sample is fitted and averaged to obtain the second corrosion current I of the first steel strip sample. C =8.3×10 -6 A / cm 2 .

[0086] The reference film porosity K0 of the first strip steel sample is calculated to be I C / I0=16.3%.

[0087] At the tail of a galvanizing unit in a cold rolling mill, six samples were cut and taken. The first strip samples to be tested were marked as 1#, 2#, and 3#, and the second strip samples to be tested were marked as 4#, 5#, and 6#.

[0088] Use absorbent cotton soaked in butanone solution to wipe the test area of ​​the first strip steel sample to be tested. The test area is a square area of ​​about 6×6cm. The angle between the tweezers and the sample is 45°. Apply a pressure of 500N, wipe at a frequency of 1 round trip / second, and stop wiping after 10 round trips in total. Then use a cold air blower to dry the residual butanone reagent on the surface.

[0089] During the test, the electrolytic cell is first placed on the surface of the first steel strip sample to be tested after wiping, and the pre-configured 3.5% NaCl solution is added to the electrolytic cell, with an injection volume of about 700 ml, and then the electrolytic cell cover with a platinum electrode mesh and a reference electrode is installed and connected to the portable electrochemical workstation. In addition, the edge of the surface of the first steel strip sample to be tested needs to be selected to grind off part of the film layer to expose the steel strip surface, and the working electrode chuck is clamped on the exposed part of the first steel strip sample to be tested, and it is also connected to the portable electrochemical workstation. After the electrolyte is injected into the electrolytic cell, it is left to stand for 5 minutes before starting to measure the polarization curve. The test parameters are: dynamic potential polarization curve scanning speed 5mv / s, potential scanning range: -1~1v (relative to the reference electrode potential), test time: 400s.

[0090] The third polarization curve spectrum of the first steel strip sample to be tested is fitted and averaged to obtain the third corrosion current I of the first steel strip sample to be tested. H =9.3×10 -6 A / cm 2 .

[0091] The porosity K of the first sample film layer of the first strip steel sample to be tested is obtained by calculation H =I H / I0×100%=18.2%.

[0092] The porosity of the reference film layer (K0) of the strip steel and the porosity of the first sample film layer (K H ) ratio, that is, the first porosity ratio α = K0 / K H =89.6%.

[0093] When 0.82≤α<0.9, it is judged that the film layer is moderately cross-linked and insufficiently cured, and the baking temperature and strip speed or coating parameters need to be adjusted immediately to improve the degree of cross-linking and curing of the coating after treatment.

[0094] Example 2

[0095] A galvanizing unit in a cold rolling mill plans to produce common galvanized products DX51-Z. Three samples of this steel without post-treatment, namely, the second steel strip samples, are obtained and degreased and dried. The electrochemical measuring device described in this application is placed on the surface of the second steel strip sample, and then a pre-configured 3% NaCl solution is added to the electrolytic cell with an injection volume of about 700 ml. Then, the electrolytic cell cover with a platinum electrode mesh and a reference electrode is installed and connected to a portable electrochemical workstation. The working electrode chuck is clamped on the edge of the sample and connected to the portable electrochemical workstation. After the three-electrode system is connected, the polarization curve measurement can be started. The test parameters are: dynamic potential polarization curve scanning speed 8mv / s, potential scanning range: -1.2~1.2v (relative to the reference electrode potential), and test time: 300s.

[0096] The first polarization curve spectra of the three second steel strip samples were fitted and averaged to obtain the first corrosion current I0=1.9×10 -5 A / cm 2 .

[0097] Post-processing standard samples were prepared for the second steel strip sample. First, the second steel strip sample was degreased, cleaned and blown dry, and then a single-sided coating of a certain type of coating was performed on the surface of the second steel strip sample using a 10μm scraper. The second steel strip sample was immediately placed in a film layer automatic temperature and time controlled oven for cross-linking and curing. The baking temperature was 210°C and the curing time was 1.5 minutes.

[0098] The prepared first steel strip sample is subjected to polarization curve measurement using the electrochemical testing device described in the present application. During the test, the electrolytic cell is first placed on the surface of the first steel strip sample, and the pre-configured 3% NaCl solution is added to the electrolytic cell, with an injection volume of about 700 ml. Then, the electrolytic cell cover with a platinum electrode mesh and a reference electrode is installed and connected to a portable electrochemical workstation. In addition, the surface of the first steel strip sample needs to select the edge part to grind off part of the film layer to expose the steel strip surface, and the working electrode chuck is clamped on the exposed part of the steel strip, and is also connected to the portable electrochemical workstation. After the electrolyte is injected into the electrolytic cell, the polarization curve measurement is started after it is allowed to stand for 5 minutes. The test parameters are: dynamic potential polarization curve scanning speed 8mv / s, potential scanning range: -1.2~1.2v (relative to the reference electrode potential), and test time: 300s.

[0099] The second polarization curve spectrum of the first steel strip sample is fitted and averaged to obtain the second corrosion current I of the first steel strip sample. C =3.6×10 -6 A / cm 2 .

[0100] The reference film porosity K0 of the first strip steel sample is calculated to be I C / I0×100%=18.9%.

[0101] At the tail of a galvanizing unit in a cold rolling mill, six samples were cut and taken. The first strip samples to be tested were marked as 1#, 2#, and 3#, and the second strip samples to be tested were marked as 4#, 5#, and 6#.

[0102] Use absorbent cotton soaked in butanone solution to wipe the test area of ​​the first strip steel sample to be tested. The test area is a square area of ​​about 6×6cm. The angle between the tweezers and the sample is 45°. Apply a pressure of 600N, wipe at a frequency of 1 round trip / second, and stop wiping after 15 round trips in total. Then use a cold air blower to dry the residual butanone reagent on the surface.

[0103] During the test, the electrolytic cell is first placed on the wiped test surface, and the pre-configured 3% NaCl solution is added to the electrolytic cell, with an injection volume of about 700ml. Then the electrolytic cell cover with a platinum electrode mesh and a reference electrode is installed and connected to the portable electrochemical workstation. In addition, the edge of the surface of the sample to be tested needs to be selected to grind off part of the film layer to expose the strip surface, and the working electrode chuck is clamped on the exposed part of the strip, and it is also connected to the portable electrochemical workstation. After the electrolyte is injected into the electrolytic cell, it is left to stand for 5 minutes before starting to measure the polarization curve. The test parameters are: dynamic potential polarization curve scanning speed 8mv / s, potential scanning range: -1.2~1.2v (relative to the reference electrode potential), test time: 300s.

[0104] The third polarization curve spectrum of the first steel strip sample to be tested is fitted and averaged to obtain the third corrosion current I of the first steel strip sample to be tested. H =3.7×10 -6 A / cm 2 .

[0105] The porosity K of the first sample film layer of the first strip steel sample to be tested is calculated H =I H / I0×100%=19.5%.

[0106] The porosity of the reference film layer (K0) of the strip steel and the porosity of the first sample film layer (K H ) ratio, that is, the first porosity ratio α = K0 / K H =96.9%.

[0107] When α≥0.96, it is determined that the film layer has no insufficient cross-linking and curing, and the electrochemical test after the tape is pulled is continued. Use 3M Scotch 600 100-grid test tape to stick and pull the test area of ​​the second strip steel sample to be tested. The test area is a square area of ​​about 6×6cm. Cover the tape on the surface of the sample and apply a pressure of 500N to wipe it. The frequency of wiping is 2 round trips / second. After a total of 10 round trips, stop wiping and then lift the tape at a speed of 2cm / s.

[0108] During the test, the electrolytic cell is first placed on the test surface of the second steel strip sample after wiping, and the pre-configured 3% NaCl solution is added to the electrolytic cell, with an injection volume of about 700 ml, and then the electrolytic cell cover with a platinum electrode mesh and a reference electrode is installed and connected to the portable electrochemical workstation. In addition, the surface of the second steel strip sample to be tested needs to select an edge position to grind off part of the film layer to expose the steel strip surface, and use the working electrode chuck to clamp the exposed part of the steel strip, and also connect it to the portable electrochemical workstation. After the electrolyte is injected into the electrolytic cell, it is left to stand for 5 minutes before starting to measure the polarization curve. The test parameters are: dynamic potential polarization curve scanning speed 8mv / s, potential scanning range: -1.2~1.2v (relative to the reference electrode potential), test time: 300s.

[0109] The fourth polarization curve spectrum of the second steel strip sample to be tested is fitted and averaged to obtain the fourth corrosion current I of the second steel strip sample to be tested. W =3.9×10 -6 .

[0110] The porosity K of the second sample film layer is calculated w =I w / I0×100%=20.5%.

[0111] The porosity of the reference film layer (K0) and the porosity of the second sample film layer (K W ) ratio, that is, the second porosity ratio β = K0 / K W =92.2%.

[0112] When β≥0.92, it is determined that the film layer has no excessive cross-linking and curing, and there is no need to adjust the post-processing process.

[0113] This application solves the technical problem that the degree of cross-linking and curing of the film layer cannot be detected efficiently and accurately after post-processing of the steel strip, and proposes an offline rapid detection device and supporting method. The device and method can quickly check on-site whether the cross-linking and curing process of the film layer on the surface of the steel strip has reached the optimal range, determine whether the film layer is insufficiently cross-linked or over-cured, and achieve quantitative characterization of the degree of cross-linking and curing. The invention can quickly and accurately evaluate the degree of cross-linking and curing of the thin film layer on the surface of the steel strip, which helps the steel mill to quickly adjust the post-processing process, reduce quality problems caused by poor film curing, and improve production efficiency and profits. The test device is simple in design, low in cost, easy to operate, and has low requirements for the testing site. The evaluation method is mature and reliable, and can be promoted and applied to the thin film layer products of almost all steel strip post-processing production lines.

[0114] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for testing the cross-linking and curing degree of a steel strip surface film layer, characterized in that: The method comprises: Obtaining the film porosity of the first steel strip sample coated with the film layer, which is defined as the reference film porosity, and the cross-linking and curing degree of the film layer on the surface of the first steel strip sample meets the industrial production requirements; Performing chemical solvent treatment on a first steel strip sample to be tested, and obtaining a film layer porosity of the first steel strip sample to be tested, which is defined as a first sample film layer porosity, wherein the first steel strip sample to be tested is obtained from an actual production line; A first porosity ratio between the porosity of the first sample and the porosity of the reference film layer is determined, and based on the first porosity ratio, it is determined whether the surface film layer of the first steel strip sample to be tested has insufficient cross-linking and curing.

2. The method according to claim 1, characterized in that The method further comprises: If the first steel strip sample to be tested does not have insufficient cross-linking and curing of the surface film layer, a second steel strip sample to be tested is subjected to a tape drawing process, and the film layer porosity of the second steel strip sample to be tested is obtained, which is defined as the second sample film layer porosity, and the second steel strip sample to be tested is produced on the same production line as the first steel strip sample to be tested; A second porosity ratio between the porosity of the second sample and the reference porosity is determined, and based on the second porosity ratio, it is determined whether the surface film layer of the second steel strip sample to be tested is excessively cross-linked and cured.

3. The method according to claim 2, characterized in that The step of obtaining the film layer porosity of the first steel strip sample coated with the film layer, which is defined as the reference film layer porosity, includes: The second steel strip sample without coating film layer is degreased, cleaned and dried; Measuring a first polarization curve spectrum of the second steel strip sample by an electrochemical measuring device, and performing fitting processing on the first polarization curve spectrum to obtain a first corrosion current of the second steel strip sample; preparing the second steel strip sample into the first steel strip sample; Measuring a second polarization curve spectrum of the first steel strip sample by an electrochemical measuring device, and performing fitting processing on the second polarization curve spectrum to obtain a second corrosion current of the first steel strip sample; The ratio of the second corrosion current to the first corrosion current is calculated as the porosity of the reference film layer.

4. The method according to claim 3, characterized in that The step of preparing the second steel strip sample into the first steel strip sample comprises: Degreasing, cleaning and drying the second steel strip sample again; Applying a film layer to the surface of the second steel strip sample by scraping with a scraper; The second steel strip sample after the coating film layer is subjected to a cross-linking and curing operation to obtain the first steel strip sample whose cross-linking and curing degree meets the requirements of industrial production.

5. The method according to claim 4, characterized in that The step of subjecting the first steel strip sample to be tested to chemical solvent treatment and obtaining the film layer porosity of the first steel strip sample to be tested, which is defined as the first sample film layer porosity, includes: Performing chemical solvent treatment on the first steel strip sample to be tested to remove the film layer material that has not solidified on the surface of the first steel strip sample to be tested; Measuring a third polarization curve spectrum of the first steel strip sample to be tested by an electrochemical measuring device, and performing fitting processing on the third polarization curve spectrum to obtain a third corrosion current of the first steel strip sample to be tested; The ratio of the third corrosion current to the first corrosion current is calculated as the porosity of the first sample film layer.

6. The method according to claim 5, characterized in that The determining, based on the first porosity ratio, whether the first steel strip sample to be tested has insufficient cross-linking and curing of the surface film layer includes: If the first porosity ratio is less than a first porosity ratio threshold, it is determined that the sample to be tested has insufficient cross-linking and curing.

7. The method according to claim 6, characterized in that The step of performing a tape drawing process on the second steel strip sample to be tested and obtaining the film layer porosity of the second steel strip sample to be tested, which is defined as the second sample film layer porosity, includes: Performing a tape pulling process on the second steel strip sample to be tested to peel off defective portions of the film layer that are not attached to the surface of the second steel strip sample to be tested; Measuring a fourth polarization curve spectrum of the second steel strip sample to be tested by an electrochemical measuring device, and performing fitting processing on the fourth polarization curve spectrum to obtain a fourth corrosion current of the second steel strip sample to be tested; The ratio of the fourth corrosion current to the first corrosion current is calculated as the porosity of the second sample film layer.

8. The method according to claim 7, characterized in that The determining whether the surface film layer of the second steel strip sample to be tested is excessively cross-linked and cured based on the second porosity ratio includes: If the second porosity ratio is less than a second porosity ratio threshold, it is determined that the second steel strip sample to be tested has excessive cross-linking and curing.

9. An electrochemical measuring device, characterized in that: The method applied to claims 1 to 8.

10. The device according to claim 9, characterized in that The device comprises: An electrolytic cell, the electrolytic cell is cylindrical, with an open upper end with a cover and a closed lower end with a hole; Portable electrochemical workstation for recording measurement data and plotting polarization curve spectra; A sealing ring, arranged at the closed hole at the lower end of the electrolytic cell; Platinum mesh electrode, reference electrode and working electrode chuck, used to connect the electrolytic cell and the portable electrochemical workstation and perform data measurement; The electrolytic cell cover is arranged at the upper open end of the electrolytic cell and is used to fix the platinum mesh electrode and the reference electrode.

Citation Information

Patent Citations

  • Method for evaluating effective porosity of metal corrosion product film

    CN103308439A

  • Method for testing porosity of surface oxide iron sheet of hot-rolled steel plate

    CN109115668A

  • Electrochemical test method for quantitative evaluation of porosity of phosphating film

    CN110361313A

  • Deposited thin films and their use in detection, attachment and bio-medical application

    CN1413261A

  • Method for testing corrosion sensitivity of metal coated substrate, involves determining corrosion sensitivity by using sample of coated substrate, such that multiple electrochemical measurement processes are performed automatically

    DE102011014909A1